Toxicity, antibacterial, and antioxidant activities of fungal Endophytes Colletotrichum and Nigrospora spp. isolated from Uvaria grandiflora - Notarte, Kin Israel R.; Devanadera, Mark Kevin P.; Mayor, Anna Beatriz R.; Cada, Mary Christine A.; Pecundo, Melissa H.; Macabeo, Allan Patrick G. (2019)
Endophytic fungi are less explored in terms of their pharmacological applications, thus screening their phytochemical constituents and biological activities is of interest. In this study, the endophytic fungi Nigrospora and Colletotrichum spp. were isolated from the leaves of Uvaria grandiflora. The identity of the endophytes was established by molecular analysis of their fungal intergenic spacer. Biological screening showed that the fungal endophytes were most active against methicillin-resistant Staphylococcus aureus (MRSA), with the ethyl acetate broth extract of Colletotrichum sp. showing the biggest zone of inhibition (ZOI) for MRSA at 19 mm. For antibacterial activity against Staphylococcus aureus, Escherichia coli, Pseudomonas aeruginosa, and Klebsiella pneumoniae, the ethyl acetate broth extract of Nigrospora sp. elicited better antibacterial activity (ZOI > 11 mm). Antioxidant assessment using 1,1-diphenyl-2-picrylhydrazyl (DPPH), ferric reducing antioxidant power (FRAP), and superoxide scavenging assays showed that Nigrospora broth extract had the best free radical scavenging activity with an IC50 of 3.92 mg/mL. Meanwhile, the broth extract from Colletotrichum sp. showed the best reducing power (RP50 = 4.41 mg/mL) and superoxide scavenging activity (SC50 = 0.78 mg/mL). Using Artermia salina for toxicity screening, both fungi were toxic having an LD50 < 0.40 mg/mL. The culture broth extracts showed greater antibacterial, antioxidant, and cytotoxic activities compared to the mycelial extracts. Phytochemical screening of the broth extract revealed the presence of flavonoids, sterols, phenols, and terpenoids in both fungal extracts. Tannins and coumarins were specifically detected in Colletotrichum sp., while alkaloids and indole derivatives were detected only in the Nigrospora endophyte.
Keywords: Antibacterial agents; Antioxidants; Fungal